COMPETENCY OF CRITICAL LITERATION OF STUDENTS LIVING IN THE BANK OF RIVER AREA IN BANJARMASIN CITY - Jumadi; Nasrullah; Syaharuddin; Mutiani; Jumriani; Abbas, Ersis Warmansyah (International Journal of Psychosocial Rehabilitation, 2020)
The main task of education is to facilitate students to be able to face their future critically and creatively. For this reason, schools should provide a variety of literacy competencies that are needed by students in order to face the increasingly complex challenges of life now and in the future. Of the many subjects given at school, language subjects, especially reading literacy material, are most responsible for being able to equip students’ literacy competencies. This study describes: (a) the level of critical literacy competency of junior high school students living in the riverbanks in Banjarmasin City; (b) the implementation of critical literacy learning towards students at SMPN who live in river areas in the city of Banjarmasin; and (c) the availability of library resources to support the improvement of critical literacy of students in schools living in river areas in Banjarmasin. This research includes a combination of quantitative and qualitative research. The determination of the sample of this study used stratified random sampling technique. The data source of this study were students and teachers who came from seven public high schools in the riverbanks in Banjarmasin City. Data collection techniques are done through tests and non tests. Quantitative data were analyzed using the SPSS program and qualitative data were analyzed by text analysis techniques.The results of the study show: the critical literacy reading competence of Banjarmasin students is low because the learning approaches used in the learning process of reading do not all lead to the implementation of a scientific approach emphasize active students. In addition, critical literacy learning materials are still focused on understanding the structure and content of the text and have not touched on a critical review of the text and the implications of the contents of the text for the purpose of community life, especially related to life on the riverbanks, and there are not adequate literature sources available to support critical literacy learning.